Wear and oxidation performances of low temperature aluminized IN600 - Yener, Tuba; Doleker, Kadir Mert; Erdogan, Azmi; Oge, Mecit; Er, Yusuf; Karaoglanli, Abdullah Cahit; Zeytin, Sakin (Elsevier Science Sa, 2022)
In this study, an aluminide coating was applied to the surface of the Inconel 600 (IN600) superalloy to improve the high-temperature oxidation and wear resistance. The low-temperature aluminizing process was carried out for 3 and 5 h at 650 and 700 C temperatures without using a protective atmosphere. A continuous and homogeneous coating has been created by providing aluminium diffusion inward in the cross-section of the alloy processed under low temperature and high activity conditions with the pack cementation method. It was observed that there was a super bonding between matrix and coating layers which are smooth, dense and porosity free. Dominant phases of Ni2Al3 and NiAl3 were detected by XRD analysis. The layer thickness was measured from the surface to the matrix and changed from 25 to 75 mu m which was increased with increasing process duration and temperature. The aluminizing process positively affected the wear resistance with the durable layers formed on the surfaces. After the isothermal oxidation tests, IN600 and aluminized IN600 show a break-away oxidation trend. The formation of the alumina layer provided better protection for aluminized samples but the formation of pits led to spallation of oxide scale in the oxidation stages.
Keywords: Ni-based superalloy; Aluminization; Microstructure; Wear; Oxidation